Removal of selected pesticides, alkylphenols, hormones and bisphenol A from domestic wastewater by electrooxidation process - Bozyigit, Gamze Dalgic; Ayyildiz, Merve Firat; Chormey, Dotse Selali; Turan, Nouha Bakaraki; Kapukiran, Fatih; Engin, Guleda Onkal; Bakirdere, Sezgin (IWA PUBLISHING, 2022)
In this study, seven compounds of environmental and health concern were treated by electrooxidation to determine their removal efficiencies from domestic wastewater. A batch type lab-scale reactor was used for the treatment process, and the analytes studied included two obsolete pesticides, two alkylphenols, two hormones, and bisphenol A. Titanium oxide and graphite electrodes were used as anode and cathode, respectively. Parameters of the electrooxidation process including pH of wastewater, ionic strength, applied current and treatment period were optimized by the univariate approach to maximize the removal efficiency of the analytes from wastewater. The optimum conditions were determined as nonadjusted pH of wastewater, 1.5 A current, 15 min treatment period and 5.0 g/L sodium chloride. Dispersive liquid-liquid microextraction was used to preconcentrate analytes before and after treatment in order to calculate the removal efficiency of analytes. The removal efficiency obtained under the optimum conditions was satisfactory for all seven analytes at different influent concentrations.
Keywords: alkylphenols; electrooxidation; endocrine disrupting compounds; hormones; pesticides; wastewater; ELECTROCHEMICAL OXIDATION; ANODE; MICROPOLLUTANTS; DEGRADATION; OZONE; Engineering; Environmental Sciences & Ecology; Water Resources